On the Possibility of Breaking the Heterodyne Detection Quantum Noise Limit With Cross-Correlation - Ernest A. Michael; Felipe E. Besser (IEEE Access, 2018)
The cross-correlation sensitivity of two identical balanced photodiode heterodyne receivers is characterized. Both the balanced photodiodes receive the same weak signal split up equally, a situation equivalent to an astronomical spatial interferometer. A common local oscillator is also split up equally and its phase difference between both the receivers is stabilized. We show by a semi-classical photon deletion theory that the post-detection laser shot noise contributions on both the receivers must be completely uncorrelated in this case of passing three power splitters. We measured the auto- and cross-correlation outputs as a function of the weak signal power (system noise temperature measurement) and obtained a cross-correlation system noise temperature up to 20 times lower than for the auto-correlation system noise temperature of each receiver separately. This is supported by Allan plot measurements showing cross-correlation standard deviations 30 times lower than in auto-correlation. Careful calibration of the source power shows that the auto-correlation (regular) noise temperature of the single balanced receivers is already very near to the quantum limit as expected, which suggests a cross-correlation system noise temperature below the quantum limit. If validated further, this experimentally clear finding will not only be relevant for astronomical instrumentation but also for other fields, such as telecommunications and medical imaging.